Analysis of Farmer Empowerment Level on Managing Paddy Farming at Tebing Village, Kelapa District, West Bangka Regency - Yulia; Robika; Fika Dewi Pratiwi (Universitas Muhammadiyah Palembang, 2025)
Empowerment of farmers is an effort to enhance farmers' abilities to carry out better farming activities through agricultural extension programs. According to the Ministerial Regulation, it is carried out in an integrated manner with agricultural development programs, namely by organizing agricultural extension to achieve an increase in farmers' empowerment so that they become prosperous. The purpose of this study is to analyze the level of empowerment of paddy farmers in Tebing Village, Kelapa District, West Bangka Regency. The research location is in Tebing Village, Kelapa District, West Bangka Regency, which was selected intentionally. Data were collected using a questionnaire instrument and analyzed using qualitative descriptive methods. The results of the study involving 35 respondents indicate that the level of farmer empowerment in Tebing Village is already good, meaning that farmers are capable of making the best decisions for themselves in carrying out farming activities and ensuring the sustainability of their farming businesses. The farmers' ability to obtain agricultural information, decision-making skills, market access skills, and adaptability are relatively high, agricultural business/financial management skills are moderately high, and partnership skills are moderate.